Identificação e caracterização de peptídeos da peçonha de serpentes botrópicas que interferem na agregação plaquetária - Simamoto, Bruna Barbosa de Sousa (2017)
Botrophs snakes represent the most important group of Brazilian venomous snakes because they are responsible for the majority of snake accidents reported in the country. In general, Bothrops poisoning is characterized by pain and edema at the site of the bite, local hemorrhage which may be accompanied by tissue and muscular necrosis, the main local complication of poisoning. Systemic bleeding and clotting disorders may also occur. In the most severe cases, shock and acute renal failure are also observed, mainly due to the hemorrhage caused. About 90% of the dry weight of snake venom corresponds to proteins and peptides, such as Lamino acid oxidases, phospholipases A2, metalloproteases, serine proteases, 5'- nucleotidases, lectins and disintegrins, which are responsible for most deleterious effects observed during poisoning. These components present different pharmacological activities, mainly on hemostasis. In recent years, a large number of snake venom toxins have been identified as interfering in platelet function, promoting or inhibiting platelet aggregation, due to their selectivity to platelet receptors, such as GPIb-V-IX, GPVI, α2β1, αIIbβ3 or to their respective linkers, such as vWF and/or fibrinogen. Detailed investigation of these molecules provides important information for the development of diagnostic tests and novel therapeutic agents for hemostatic disorders. The present work aimed to identify and characterize new venom toxins from Bothrops snake venom capable of interfering in platelet function. As a result, two peptides named BaltPAi and BmooPAF isolated from Bothrops alternatus and Bothrops moojeni snake venom, respectively, were identified. BaltPAi is a peptide capable of inhibiting collageninduced platelet aggregation. In addition, BaltPAi also showed cytotoxic effect on human cervical adenocarcinoma cells (HeLa) and human prostate adenocarcinoma cells (PC-3). In turn, BmooPAF is a peptide capable of inducing platelet aggregation via GPIbα. These small peptides have attracted the attention and interest of pharmaceutical companies that search for new drugs because of their simpler structures and therapeutic potential which can be easily synthesized and at a low cost. These properties make them particularly suitable probes for the development of novel pharmacological drugs.